Geology of Las Minas: an example of an exhumed geothermal system (Eastern Trans-Mexican Volcanic Belt). Issue 2 (9th December 2020) - Olvera-García, Emmanuel; Bianco, Caterina; Víctor Hugo, Garduño-Monroy; Brogi, Andrea; Liotta, Domenico; Wheeler, Walter; Gómez-Alvarez, Fidel; Najera-Blas, Sergio; Jiménez-Haro, Adrián; Guevara-Alday, Jorge Alejandro; Bastesen, Eivind; Lepillier, Baptiste; et al.
ABSTRACT: The Las Minas area corresponds to an exhumed geothermal system considered a proxy for the deep part of the nearby Los Humeros active geothermal system. The stratigraphic succession is made up of: Palaeozoic-Miocene granitoids, a thick Jurassic- Cretaceous carbonate succession, Neogene lava flows and volcano-sedimentary deposits. Linked to a Miocene magma intrusion, marble and skarn rock-volumes developed by contact metamorphism and geothermal fluid flow. Faults are arranged in SW- and NNW-striking systems. These controlled the morphological evolution and favored Neogene-Quaternary dyke emplacement. Faulting gave rise to a tectonic depression where lacustrine sediments and pyroclastics deposited. Skarn rocks are mainly located at fault intersections and along pre-existing discontinuities, suggesting the role of bedding and/or fractures in channeling deep fluids. Results give inputs for exploration at depth of Los Humeros geothermal system.